2016
DOI: 10.1210/jc.2016-2246
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Quality of Life in Adult Survivors of Pediatric Differentiated Thyroid Carcinoma

Abstract: Overall, long-term QoL in survivors of pediatric DTC was normal. Survivors experienced mild impairment of QoL in some domains (physical problems, mental fatigue, and various thyroid cancer-specific complaints). Factors possibly affecting QoL need further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 35 publications
3
62
0
3
Order By: Relevance
“…However, our study has some potentially important improvements compared with these previous reports. [ 10 , 15 , 18 ] First, we compared the baseline HRQoL of 186 PTC patients with that of the 186 subjects from the general population and found that all 8 domains of HRQOL were lower in the PTC patients; 7 domains were significantly different. Second, we have identified PTC and diabetes or hypertension as risk factors for lower HRQOL scores.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study has some potentially important improvements compared with these previous reports. [ 10 , 15 , 18 ] First, we compared the baseline HRQoL of 186 PTC patients with that of the 186 subjects from the general population and found that all 8 domains of HRQOL were lower in the PTC patients; 7 domains were significantly different. Second, we have identified PTC and diabetes or hypertension as risk factors for lower HRQOL scores.…”
Section: Discussionmentioning
confidence: 99%
“…The favourable outcomes for young adults with phenylketonuria and females with Fabry disease could be that these diseases have few long‐term somatic effects if they are treated successfully . The excellent prognosis and low school absence rate could explain the favourable psychosocial development of young adults treated for differentiated thyroid carcinoma . With regard to vitiligo, it is interesting to note that patients who had negative experiences with their vitiligo during childhood did show any delay in their social development …”
Section: Discussionmentioning
confidence: 99%
“…For the nationwide study, all patients diagnosed with DTC at age ≤18 years between 1970 and 2013 treated in the Netherlands were included ( 5 ). Exclusion criteria were, as previously reported: follow-up <5 years after diagnosis, attained age <18 years, diagnosis of DTC as a second malignant neoplasm, lack of understanding of the Dutch language, and 131-I administration within three months before evaluation ( 19 ). For the current study, survivors aged >35 years during evaluation were also excluded because the questionnaire is validated only up to the age of 35 years ( 7 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although we preferred peers (e.g. friends, colleagues), we allowed inclusion of family members, provided they met the in/exclusion criteria ( 19 ). For the current substudy, peer controls aged >35 years were also excluded.…”
Section: Methodsmentioning
confidence: 99%